Molecular orientation and dielectric anisotropy properties of 4-cyano-4?-n-heptylbiphenyl-TiO2 liquid crystal composite - Okutan, M.; Yakuphanoğlu, Fahrettin; Koysal, O.; San, S. E.; Oweimreen, G. A. (Elsevier Science Bv, 2008)
The molecular orientation and the dielectric anisotropy of the nematic liquid crystal (LC) 4-cyano-4'-n-heptylbiphenyl (7CB) and of TiO(2)-doped 7CB have been investigated. The dielectric properties of the LCs exhibit a relaxation peak that shifts to lower frequencies with increasing voltages. The relaxation frequencies of 7CB and 7CB/TiO(2) liquid crystals were calculated and found to decrease as the bias voltage increases. This is attributed to molecular reorientation. The dielectric anisotropy of the LCs changes from the positive type to negative type and the static electric permittivity and dielectric anisotropy values were found to be lower for the 7CB/TiO(2) system. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: dielectric properties, relaxation, electric modulus; liquid crystals and molecular liquids